POPULASI HAMA PENGGEREK TONGKOL JAGUNG Helicoverpa armigera (LEPIDOPTERA : NOCTUIDAE) DI KABUPATEN BONE BOLANGO PROVINSI GORONTALO - Tuliabu, Ramlan; Pelealu, J.; Kaligis, J. B.; Dien, M. F. (EUGENIA, 2015)
ABSTRACT Helicoverpa armigera is one of the important pests in maize in Gorontalo province. The study aims to determine the population of corn cob borer Helicoverpa armigera has been implemented in Bolango Bone regency, Gorontalo Province from March to June 2011 study used a survey method based on the four zoning districts as follows: (1) the northern region districts Tilong Kabila, (2 ) Suwawa Western region districts namely, (3) the Eastern region districts Kabila, and (4) the South region, namely districts Bone Pante. The results showed that the average population of H. armigera cob borers on maize in Bone regency Bolango highest in the district is 3.75 Kabila Bone tail, then the tail 1.92 Tilongkabila districts, sub-districts and districts tail Kabila 1.83 Suwawa 1,4 tail. Keywords: Helicoverpa armigera, pest population